Portfolio Managers and Elections in Emerging Economies: How investors dislike political uncertainty - Emmanuel Frot; Javier Santiso (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2010)
This paper studies the effect of elections and democracy on bond and equity flows to emerging countries. Our results indicate that elections affect portfolio flows: the period following an election is generally characterised by a fall in equity flows, and this occurs only where the incumbent is not re-elected. We interpret this result as evidence that political uncertainty about future policies plays a key role in explaining the effect of elections. Bond flows decrease after an election that brings a change of ideology in government, with some evidence that this effect is stronger if such change is from right- to leftwing. This set of results suggests that investors value continuity and stability in the political environment, and dislike changes. Finally, democracy, in itself, is not found to significantly influence portfolio equity and bond flows, such that there is no democratic premium. On the other hand, a decrease in the democracy score implies lower equity flows. Investors value continuity (stable democracy level, even if low) rather than improvements (democratic transitions) but are responsive to a deterioration in the democratic environment that is often accompanied by less transparency, and therefore greater uncertainty.
Keywords: F59; G11; G15; 330; Portfolio decisions; Elections